Appréciation de l’aptitude fromagère des laits de vaches individuelles de la ferme expérimentale : Test d’aptitude fromagère et de rendement fromager - ATTARI, Sihem (My University, 2019)
The studyinvolved a follow-up and hygienic and microbiological control of fresh milk produced by the Hassi-Mamèche University affiliated experimental farm from 02 holsteinprimlactating dairy cows. The objectives of this study are to test the time-over-thedate repeatability of cheese-based aptitude tests (coagulation-yielding cheese) used on individual milks on the experimental farm compared to thosere constructed with milk powder cheese and try to explain these cheese aptitude tests with simple criteria of milk composition, such as protein content, to study the real impact of fat and mineral matter on clottingability (repeatabilityspread over 4 weeks). The physical and chemical results obtained are generally not in accordance with F.I.L. standards (in terms of protein and mineralmaterialrichness). From a bacteriological and hygienic point of view, this milk has an un acceptable quality. Indeed, the total flora count shows that the samples have a total flora above the standard whichis set at 3,105 UFC/ml. The coliform count revealed a presence of 38 to 150 germs/ml. For Staphylococci and Butyrics their presenceis not recommended by the standard and for dairy processing. The presence of these floras shows that breeding and hygiene practices need to beimprovedat all levels. The repeatability of the physical-chemical measures on fresh milk allowed us to confirm the results for the adaptation-orientation of our milks produced to cheese processing by a protein amendment with milkre constituted from a powder cheese milk provides the balance needed for properclotting and the expected cheeseyield.
Keywords: fresh milk; physical-chemical quality; microbiological quality and cheese aptitude tests